Feeding behaviour, risk-sensitivity and response control: effects of 5-HT2C receptor manipulations. (18th February 2019) - Humby, Trevor; Patel, Yateen; Carter, Jenny; Stokes, Laura-Jean G.; Rogers, Robert D.; Wilkinson, Lawrence S.
Abstract : People, like animals, tend to choose the variable option when given the choice between a fixed and variable delay to reward where, in the variable delay condition, some rewards are available immediately (Laura-Jean et al . 2019 Phil. Trans. R. Soc. B 374, 20180141. (doi:10.1098/rstb.2018.0141 )). This bias has been suggested to reflect evolutionary pressures resulting from food scarcity in the past placing a premium on obtaining food quickly that can win out against the risks of sometimes sustaining longer delays to food. The psychologies mediating this effect may become maladaptive in the developed world where food is readily available contributing, potentially, to overeating and obesity. Here, we report our development of a novel touchscreen task in mice allowing comparisons of the impact of food delay and food magnitude across species. We show that mice exhibit the typical preference, as shown by humans, for variable over fixed delays to rewards but no preference when it comes to fixed versus variable reward amounts and further show that this bias is sensitive to manipulations of the 5-HT2C receptor, a key mediator of feeding and impulse control. We discuss the data in terms of the utility of the task to model the psychologies and underlying brain mechanisms impacting on feeding behaviours. This article is part of the theme issue 'Risk taking and impulsive behaviour: fundamental discoveries, theoretical perspectives and clinical implications'.